(untitled) (Journal of Information Technologies in Education (ITE), 2008)
In article questions of improvement of preparation master’s degree by means of resources of a network the Internet are staticized, the domestic and foreign resources the Internet focused on training master’s degree are analysed; it is classified national Internet resources.